1993
DOI: 10.1126/science.7694367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by cAMP of Ras-Dependent Activation of Raf

Abstract: Activation of the Raf and extracellular signal-regulated kinases (ERKs) (or mitogen-activated protein kinases) are key events in mitogenic signalling, but little is known about interactions with other signaling pathways. Agents that raise levels of intracellular cyclic adenosine 3',5'-monophosphate (cAMP) blocked DNA synthesis and signal transduction in Rat1 cells exposed to epidermal growth factor (EGF) or lysophosphatidic acid. In the case of EGF, receptor tyrosine kinase activity and association with the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
583
5
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 911 publications
(636 citation statements)
references
References 38 publications
47
583
5
1
Order By: Relevance
“…Although 5 735 could be phosphorylated by protein kinase A, the physiological significance of the phosphorylation of RID is not known. In contrast, the phosphorylation of Raf-I by protein kinase A reduced its binding to ras p21 [33,34]. The decrease of the affinity of Raf-1 for ras p21 by protein kinase A might be one of the mechanism by which the signals through cyclic AMP inhibit the proliferation of the cells [35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although 5 735 could be phosphorylated by protein kinase A, the physiological significance of the phosphorylation of RID is not known. In contrast, the phosphorylation of Raf-I by protein kinase A reduced its binding to ras p21 [33,34]. The decrease of the affinity of Raf-1 for ras p21 by protein kinase A might be one of the mechanism by which the signals through cyclic AMP inhibit the proliferation of the cells [35].…”
Section: Discussionmentioning
confidence: 98%
“…the interaction ofras p21 and rapl p21 with RID It has been known that Raf-1 is phosphorylated by protein kinase A and that phosphorylation of Raf-1 reduces the binding of Raf-1 to ras p21 [33,34]. Therefore, we examined whether protein kinase A affects the interaction of RGL with ras p21 and rapl p21.…”
Section: Effect Of the Phosphorylation Of Rid By Protein Kinase A Onmentioning
confidence: 99%
“…In addition, cAMP also inhibits insulin and growth-factor-stimulated MAPK signalling in most cell types [25,[37][38][39][40], with the exception of Swiss 3T3 and PC12 cells (reviewed in [25]). Our previous studies have shown that SpcAMP counter-regulates insulin's effect on PP-2A inactivation by decreasing the tyrosine phosphorylation of PP-2A and restoring its catalytic activity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of Raf has been observed previously both at the level of activation and with active Raf. Phosphorylation of c-Raf-1 on Ser-43 of the regulatory domain trough PKA inhibits the Ras dependent activation of Raf-1 kinase leading to the downregulation of the classic cascade and to inhibition of growth factor induced cell proliferation of Ratla and NIH 3T3 cells [12,29,30]. Inactivation of constitutively active c-Raf-1 was observed in Jurkat T-cells [31].…”
Section: Discussionmentioning
confidence: 99%